STUDENTS PERCEPTION BY USING GOOGLE FORMS-BASED ENGLISH ASSESSMENT IN ENGLISH ACADEMIC - Arisman Arisman; Syafryadin Syafryadin (Universitas Khairun, 2023)
This study aims to investigate how students perceive the utility-perceived self-efficacy, perceived cheating risk, and of online formative assessment using Google Forms. Additionally, it aims to assess the benefits and drawbacks of using Google Forms as an online formative assessment tool for EFL teachers. This study was a quantitative. investigation into how senior high school students felt about teachers utilizing Google Forms to evaluate their students. The population of this study is student senor high school in Seluma. The sample in this study were 40 students. a perception survey that offered The attitudes of senior high school students were assessed employing a 10-item online survey divided into three variables: perceived self-efficacy (three statements), perceived cheating risk (four words), and perceived utility (four statements) (three statements).According to the poll results, 23.5% of the majority of students said that using Google Forms helped them learn to read and made that process easier. Regarding her use of Google Forms, her 11.25% of students were neutral, 15.5% of students disagreed, 8.25% of students definitely disagreed, and 42% of students strongly agreed. The findings revealed many drawbacks to utilizing Google Forms as well as students' perceptions that using it positively enhances learning despite the possibility of cheating. In order to track each student's development during the course and create interventions to prevent cheating on online tests, English language teachers are recommended to involve all students in online formative assessments. The current study contributes to greater knowledge of the benefits and drawbacks of English online testing.